AN ESTIMATION OF COMFORT APPLICATION OF SOFTWARE IN CONTEXT OF AGILE-DEVELOPMENT - Сидоров, М. О.; Гученко, І. В. (Science-based technologies, 2010)
The article is dedicated to designing of a technique for usability automated evaluation under agile software design for the purpose of taking into account and predicting user’s requests. Specified technique allows not only to estimate a current usability level of software systems, but also to manage quality of their creation processes on the basis of mathematical optimization models.